Evaluation of pharyngeal swallowing pressure using high-resolution manometry during transoral surgery for oropharyngeal cancer. Issue 2 (8th February 2021) - Fujiwara, K; Koyama, S; Taira, K; Kawamoto, K; Fukuhara, T; Takeuchi, H
Abstract: Background: Transoral robotic surgery is frequently described, driven by the desire to offer a less morbid alternative to chemoradiation. However, the objective evaluation of post-operative function has rarely been reported. Therefore, high-resolution manometry was used in this study to evaluate the impact of changes in peri-operative swallowing function on pharyngeal pressure events. Methods: Ten patients with various stages of oropharyngeal cancer underwent transoral surgery. High-resolution manometry and videofluoroscopic swallow studies were performed before surgery and two months afterwards. The following parameters were obtained: velopharyngeal and mesopharyngeal post-deglutitive upper oesophageal sphincter pressures, velo-meso-hypopharyngeal contractile integral, upper oesophageal sphincter relaxation pressure, and pharyngeal velocity. Results: There was no significant difference in pharyngeal pressure or contractile integral pre- versus post-operatively. However, pharyngeal velocity was significantly higher post-operatively than pre-operatively. Conclusion: High-resolution manometry showed that transoral surgery in patients without pre-operative dysphagia preserved pharyngeal constriction. However, transoral surgery might produce scar formation in the pharynx, which could lead to narrowing of the pharynx.